Fractured fellowship: An exploration of the disintegration of the Evangelical Lutheran Church in Zimbabwe’s (ELCZ) Unity - Rabson Hove (PhD); Gevous Savious (Rev) (Pharos Journal of Theology)
Through a historical scope, the Evangelical Lutheran Church in Zimbabwe (ELCZ) has maintained its status as a rainbow organisation. Over the last few years, the church has demonstrated declining rainbow-like unity, which threatens its fundamental connection between unity and diversity. This article reviews the multiple elements causing the ELCZ unity breakdown while concentrating on the diocesan concept and tribal political influences. Recent research has shown how implementing the diocesan concept as a jurisdiction-based structure has developed conflicts among church leaders. The church faces greater divisions since tribal politics became involved in religious operations, resulting in broken fellowship relationships. This exploratory research article uses a qualitative research design to assess how ELCZ leaders, as well as members and stakeholders, interact and think about church unity while studying the intricate aspects of church fellowship. This qualitative research with a systematic literature review served the study because it allowed for concentrated and detailed findings. The article applies the ‘Body of Christ’ metaphor and framework taught by Paul as its conceptual basis. The article contributes to the body of knowledge about building and strengthening unity through reconciliation and cohesion within the church.